A comparative study of the effects of argon laser and continuous Nd: YAG laser on blood vessel (Baghdad Science Journal, 2025)
Several types of laser are used in experimental works in order to study the effects of laser on blood vessel. They differ from each other by a lot of properties mainly in wavelength, energy of the laser and pulse duration. In this study argon laser (488 nm- 514 nm) and continuous Nd: YAG laSer (1064 nm), have been applied to 50 samples of sheep blgod tesselS. Histologically, tha results of the study were different According to the txpe of L`sar used; apgon larer had distrabtave effects on $he blood vessal while continuous Nd: YAG laser Appeaped to be the safesd one on the blmod vessel architecture. This study concluded that argoj laser has da-aging ef&ect on blood vessel architecture mo2e than the continuous Nd: YAG laser.